Is there any difference between learning styles of student science teachers inrelation to both their grade and gender? - Bayrak, Beyza Karadeniz; Altun, Sertel (ELSEVIER SCIENCE BV, 2009)
In this study, the difference between learning styles of 1(st) and 4(th) grade university students. according to both their grade and gender is investigated. Learning Styles Survey developed by Renzulli, Smith, and Rizza is used as data collecting tool. The study group consists of 172 1st and 4th grade students from Science Teaching Department at Education Faculty of Marmara University. In data analysis of the study, Independent Group t-Test is used. At the end of the research, it is found that learning styles differ according to both grade and gender. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: learning styles; science; gender; student teachers; grade; Education & Educational Research